Optimisation of Varian TrueBeam head, thorax and pelvis CBCT based on patient size. Issue 3 (5th September 2021) - Agnew, Christina E.; McCallum, Candice; Johnston, Gail; Workman, Adam; Irvine, Denise M.
Abstract: Purpose: The aim of this study was to optimise patient dose and image quality of Varian TrueBeam cone beam computed tomography (CBCT) pelvis, thorax and head and neck (H&N) images based on patient size. Methods: An elliptical phantom of small, medium and large size was designed representative of a local population of pelvis, thorax and H&N patients. The phantom was used to establish the relationship between image noise, CT and CBCT exposure settings. Using this insight, clinical images were optimised in phases and the image quality graded qualitatively by radiographers. At each phase, the time required to match the images was recorded from the record and verify system. Results: Average patient diameter was a suitable metric to categorise patient size. Phantom measurements showed the power relationship between noise and CBCT exposure settings of value −0·15, −0·35 and −0·43 for thorax, pelvis and H&N, respectively. These quantitative phantom measurements provided confidence that phased variation of ~±20% in mAs should result in clinically usable images. Qualitative assessment of almost 2000 images reduced the exposure settings in H&N images by −50%, thorax images by up to −66% and pelvis images by up to −80%. These optimised CBCT settings did not affect the time required to match images. Findings: Varian TrueBeam CBCT mAs settings have been optimised for dose and image quality based on patient size for three treatment sites: pelvis, thorax and H&N. Quantitative phantom measurements provided insight into the magnitude of change to implement clinically. The final optimised exposure settings were determined from radiographer qualitative image assessment.